The Use Of Foley Catheters In Epistaxis. A Question Of Informed Consent - Hussein M. Hassan (مجلة كلية الطب, 2006)
Background The Medicines and Health care products Regulatory Agency stated in 2003 that doctors should endeavor to avoid using products in treatments not covered by their product license. Foley catheters are commonly used in the management of epistaxis although their product license does not cover this. Aims : To study the extent of the use of these catheters and the knowledge that otolaryngologists had of their legal status. Method : By undertaking a questionnaire survey of some Otolaryngologists in Baghdad Results : Most members appear to use Foley catheters in the management of epistaxis; however most of them are not aware that the product is not licensed for this purpose. Because of this lack of knowledge, only few obtain verbal consent for treatment with this device and none of the surveyed members obtain written consent from patients. Conclusion :In the era of increasing litigation, documentation of informed consent could be considered mandatory to protect us from possible legal action, and this needs to be known by all practicing Otolaryngologists.